A Photoswitchable Dualsteric Ligand Controlling Receptor Efficacy. Issue 25 (16th May 2017) - Agnetta, Luca; Kauk, Michael; Canizal, Maria Consuelo Alonso; Messerer, Regina; Holzgrabe, Ulrike; Hoffmann, Carsten; Decker, Michael
Abstract: The investigation of the mode and time course of the activation of G‐protein‐coupled receptors (GPCRs), in particular muscarinic acetylcholine (mACh or M) receptors, is still in its infancy despite the tremendous therapeutic relevance of M receptors and GPCRs in general. We herein made use of a dualsteric ligand that can concomitantly interact with the orthosteric, that is, the neurotransmitter, binding site and an allosteric one. We synthetically incorporated a photoswitchable (photochromic) azobenzene moiety. We characterized the photophysical properties of this ligand called BQCAAI and investigated its applicability as a pharmacological tool compound with a set of FRET techniques at the M1 receptor. BQCAAI proved to be an unprecedented molecular tool; it is the first photoswitchable dualsteric ligand, and its activity can be regulated by light. We also applied BQCCAI to investigate the time course of several receptor activation processes. Abstract : A dualsteric acetylcholine receptor ligand that interacts with two binding sites of the receptor and contains a photoswitchable azobenzene unit was synthesized. FRET studies reveal that the activity of the ligand can be reduced with light and that it represents an unprecedented molecular tool to investigate the time course of receptor activation processes.